1993
DOI: 10.1002/pola.1993.080310917
|View full text |Cite
|
Sign up to set email alerts
|

Polyimides with alicyclic diamines. I. Syntheses and thermal properties

Abstract: The polyaddition reactions of alicyclic diamines such as 1,4‐diaminocyclohexane (1,4‐CHDA) or 4,4′‐diaminodicyclohexylmethane (DCHM) and configurational isomers of 1,4‐CHDA or DCHM with tetracarboxylic aromatic anhydrides in aprotic solvents were carried out to prepare high molecular weight poly(amic acid)s. Through the thermal imidization of poly(amic acid)s, several flexible polyimide films were prepared. Because of the stiffness of the alicyclic moieties in diamines, the resulting polyimides exhibit high gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 82 publications
(77 citation statements)
references
References 9 publications
2
75
0
Order By: Relevance
“…4n the other hand, polyimides prepared from alicyclic diamines also have high transparency due to the weak electron donating ability of alicyclic diamines. Jin et al [14,15] have prepared alicyclic polyimides from 4,4'-diaminodicyclohexylmethane (DCHM) together with pyromellitic dianhydride (PMDA), biphenyltetracarboxylic dianhydride (BPDA), and benzophenonetetracarboxylic dianhydride (BTDA). They found that alicyclic polyimides showed not only high transparency but also high physical thermal stability.…”
Section: Introductionmentioning
confidence: 99%
“…4n the other hand, polyimides prepared from alicyclic diamines also have high transparency due to the weak electron donating ability of alicyclic diamines. Jin et al [14,15] have prepared alicyclic polyimides from 4,4'-diaminodicyclohexylmethane (DCHM) together with pyromellitic dianhydride (PMDA), biphenyltetracarboxylic dianhydride (BPDA), and benzophenonetetracarboxylic dianhydride (BTDA). They found that alicyclic polyimides showed not only high transparency but also high physical thermal stability.…”
Section: Introductionmentioning
confidence: 99%
“…The values of Tg for PI(TCAAH/ DPM), PI(TCAAHI6FdA) and PI(TCAAHJ DCHM) obtained from TMA curves are summarized in Table I. Compared to a conventional aromatic polyimide, e.g., PI(PMDA/DPM) with Tg = 336°C by TMA, [15] the introduction of alicyclic dianhydride TCAAH into the polyimide main chains, did not change the Tg values so much. PI(TCAAH/DPM) and PI(TCAAH/6FdA) show almost similar thermomechanical behavior under heating, whereas PI(TCAAH/DCHM) shows T g at a lower temperature, which suggests that introduction of the alicyclic DCHM to the TCAAHbased polyimide backbone has affected the thermomechanical behavior of the polyimides.…”
Section: Thermal Properties Of Tcaah-based Polyimidesmentioning
confidence: 99%
“…Because of the asymmetric and bulky structure, TCAAH would prefer to a non-coplanar structure. DCHM [15] is a mixture of trans-trans, trans-cis, cis-cis isomers. So the conformation of PI (TCAAHIDCHM) would be very complicated and includes various non-coplanar packing structure due to various degrees of constraint formation.…”
Section: Fluorescence Spectra Of Polyimide Filmsmentioning
confidence: 99%
“…The difference in these ratios can be attributed to the difference in the reactivity of disproportionation between benzophenone ketyl radical and alkyl radical (14).…”
Section: Photochemistry Of Benzophenone-type Photosensitive Polyimidesmentioning
confidence: 99%